Application of Chinese milk vetch affects rice yield and soil productivity in a subtropical double-rice cropping system - Jing-rui CHEN; Wen-jing QIN; Xiao-fen CHEN; Wei-dong CAO; Guo-min QIAN; Jia LIU; Chang-xu XU (Journal of Integrative Agriculture, 2020)
Green manure can be used as a substitute for chemical fertilizer without reducing rice yield. We studied the responses of soil fertility and rice yield to different combinations of Chinese milk vetch (CMV; Astragalus sinicus L.) and chemical fertilizer in a subtropical double-rice cropping system. Our goal is to reduce chemical fertilizer use and decrease environmental contamination. Compared with the recommended rate of chemical fertilizer (CF), both early- and late-rice yields in the two treatments supplied with 15 and 22.5 Mg CMV ha−1 plus 60% CF (represented as 60A and 60B, respectively) showed no significant differences while the two treatments supplied with 30 and 37.5 Mg CMV ha−1 plus 60% CF (represented as 60C and 60D, respectively) showed significantly higher values. The sustainable yield index (SYI) values in the 60C and 60D treatments with double-rice croppong system were significantly higher than those in other treatments (P<0.05). Early-rice yield showed a significant positive relationship with the Chinese milk vetch incorporation rate. The coefficients increased annually from 2009 to 2013 and then decreased in 2014. Soil organic matter increased over time by the end of the experiment in all of the treatment groups. Soil organic matter in 60A, 60B and 60C showed no significant difference compared with that in CF, while soil organic matter in 60D was significantly higher than that in CF. The slopes of soil organic matter and total nitrogen over six years were the highest in 60C and 60D. The soil total nitrogen content in 60A, 60B, 60C and 60D was higher than that in CF, but the differences were not significant (P>0.05). Therefore, a relatively high Chinese milk vetch incorporation rate (≥30 Mg ha−1) was more effective in improving the productivity and sustainability of paddy soil. The decreased coefficients of early-rice yield and the Chinese milk vetch incorporation rate in 2014 implied that the benefits of soil fertility and rice yield created by Chinese milk vetch input may decline after five years under a continuously high rate of Chinese milk vetch incorporation.